Eksplorasi Etnomatematika Kain Tapis Lampung - Masturina Hamid, Ellya; Mariani, Scolastika; Agoestanto, Arief (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2023)
Indonesia has a very large and diverse range of cultural diversity. Ethnomathematics has a very important role in introducing culture to students by studying the mathematical elements that exist in it. The purpose of the research is to explore the mathematical elements contained in Lampung tapis fabric. The method used in this research is literature review and descriptive analysis. Based on the results of the analysis and discussion, it is found that Lampung tapis fabric contains mathematical elements in which students can learn mathematical materials such as flat shapes, geometric transformations and in this study examples of problems related to geometric shapes found in tapis fabric are presented.